A study of the vegetative and reproductive responses of Prunus Armeniaca cultivar Peeka to hydrogen cyanamide - Bergh, Anton Oloff Denis (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1989.